Juridical Review for Buyers in Sale and Purchase Agreements Via E-Commerce when A Default Occurs - Ricky Indoladeshi; Puguh Aji Hari Setiawan; Tarmudi Tarmudi (Rechtenstudent, 2024)
The issues discussed are regarding regulations regarding consumer protection in electronics transactions in Indonesia, legal protection for consumers who suffer losses in purchasing and selling transactions on line shopping sites, responsibility of shopping site managers for losses experienced by consumers when making purchase and selling transactions through on-line shopping sites. The data collection method is data from various reading sources, such as legislation, books, scientific journals, and the internet whose value is relevant to the problems discussed. Based on the research results obtained, it shows that regulations regarding consumer protection in electronics transactions in Indonesia can be properly accommodated by the Consumer Protection Law and the Information and Electronic Transactions Law which is realized through the protection of consumer personal data, conditions for the validity of e- commerce transactions, standard clauses, and regulations regarding e-commerce transactions objects.